2021
DOI: 10.1021/acsanm.1c03110
|View full text |Cite
|
Sign up to set email alerts
|

MoOx-Decorated ZrO2 Nanostructures Supporting Ru Nanoclusters for Selective Hydrodeoxygenation of Anisole to Benzene

Abstract: Currently, the hydrodeoxygenation (HDO) process of biomass-derived phenolics is regarded as one of the most promising methods of upgrading to produce various high-value-added chemical raw feeds (e.g., benzene, toluene, and xylene) as well as potentially applied bio-oils with less oxygen content. In this work, a series of surface MoO 3decorated nanosized tetragonal zirconia (t-ZrO 2 ) supports were utilized to immobilize Ru nanoclusters for the aqueous-phase HDO of anisole. Structural characterizations revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…57,58 The pathway of the direct hydrogenolysis of phenolics to arenes is easier when Ru-based and metal sulfide catalysts are used. 19,43,59,60 According to the reaction network, the highly efficient production of arenes can be furnished by designing the unique catalysts and controlling the reaction conditions to enhance the direct C−O bond cleavage capability or inhibit the ring hydrogenation steps. BTX are three typical arene compounds produced from the catalytic HDO of lignin-derived phenolics and belongs to the seven core segments of the petrochemical industry with a production capacity of a 10 000 ton scale worldwide.…”
Section: Lignin-derived Phenolicsmentioning
confidence: 99%
See 1 more Smart Citation
“…57,58 The pathway of the direct hydrogenolysis of phenolics to arenes is easier when Ru-based and metal sulfide catalysts are used. 19,43,59,60 According to the reaction network, the highly efficient production of arenes can be furnished by designing the unique catalysts and controlling the reaction conditions to enhance the direct C−O bond cleavage capability or inhibit the ring hydrogenation steps. BTX are three typical arene compounds produced from the catalytic HDO of lignin-derived phenolics and belongs to the seven core segments of the petrochemical industry with a production capacity of a 10 000 ton scale worldwide.…”
Section: Lignin-derived Phenolicsmentioning
confidence: 99%
“…Arenes, such as benzene, toluene, and xylene (BTX), are a versatile class of raw materials for chemical production and are widely used in the fuel, rubber, fiber resin, pharmaceutical, textile, fragrance, and paper industries. At present, the preparation of arenes is generally dependent on nonrenewable fossil resources (Figure a). The excessive reliance on fossil feedstocks has led to the problems of an energy crisis and environmental deterioration, which promotes the development of green and sustainable energy sources. Particularly, the production of arenes from renewable biomass has the advantages of low pollution and greenhouse gas emission, while the petroleum refining process produces large amounts of byproducts and other toxic gases and wastes, which seriously pollute the environment. Biomass, as a cheap and abundant renewable resource in nature, can be translated into various value-added functional chemicals and fuels. Accordingly, under the global theme of advocating both carbon neutrality and low carbon economy, the utilization of biomass resources to produce high-valued arenes has attracted great interest and attention from researchers worldwide (Figure b). …”
Section: Introductionmentioning
confidence: 99%
“…The synergistic participation of SnO 2 and NiO in NiO(10%)/SnO 2 provides the appropriate & modulated acid–base surface (Ni δ+ , Sn δ+ , and O δ‑ ) and oxygen vacancy on the catalyst surface for the efficient adsorption and activation of BPE and the Lewis acid/base site to activate isopropanol. Several theoretical and experimental studies have demonstrated that the oxygen vacancies on the catalyst surface facilitate the adsorption of the lignin oxygenate. , It is further known that isopropanol offers its hydrogen from its hydroxyl group as mobile hydrogen to initiate the transfer hydrogenolysis process (Scheme ). , Moreover, the theoretical investigation demonstrated that the more feasible hydrogenolysis intermediates of BPE were the benzyl and phenoxy radicals due to its lower bond dissociation energy of 184.3 kJ/mol, whereas the two other intermediates phenyl and benzyloxy radicals & benzyl cation and phenoxy anions were not favorable due to their higher bond dissociation energy of 332.9 and 627.7 kJ/mol, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Plausible Mechanism for CTH of BPE. 61,62 It is further known that isopropanol offers its hydrogen from its hydroxyl group as mobile hydrogen to initiate the transfer hydrogenolysis process (Scheme 2). 51,63 Moreover, the theoretical investigation demonstrated that the more feasible hydrogenolysis intermediates of BPE were the benzyl and phenoxy radicals due to its lower bond dissociation energy of 184.3 kJ/mol, whereas the two other intermediates phenyl and benzyloxy radicals & benzyl cation and phenoxy anions were not favorable due to their higher bond dissociation energy of 332.9 and 627.7 kJ/mol, respectively.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…A weak absorption at 2132–2142 cm −1 is assignable to CO species bound to Ru 4+ sites ( i. e ., Ru (CO) 4 ), [39,40] while another small band at ∼2072 cm −1 is associated with CO species linearly adsorbed at Ru δ+ sites. Meanwhile, an intense absorption at ∼2028 cm −1 is assignable to CO linearly adsorbed at Ru 0 sites, [41,42] and the absorption of bridge‐adsorbed CO at Ru 0 sites appears at ca . 1935–1952 cm −1 [11,43] .…”
Section: Surface‐interface Properties Of Ru‐based Samplesmentioning
confidence: 99%